2022
DOI: 10.1039/d2cp01777f
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient blue quantum-dot light-emitting diodes based on a mixed composite of a carbazole donor and a triazine acceptor as the hole transport layer

Abstract: Solution-processed thermally activated delayed fluorescence (TADF) exciplexes were employed as hole transport layer (HTL) of blue quantum dot (QD) light-emitting diodes (QLEDs) by blending polymer donors of poly(N-vinylcarbazole) (PVK) with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Compared to the neat PVK film, the emission of the blended films exhibits a much narrower and slight red shift in DPPE:PVK films. This indicates a change in the bandgap and the absence of excess heteroemission. ,, The PL peaks of blue QDs on PVK and DPPE:PVK films are identical to the PL peak in the neat blue QDs film, which is observed at 450 nm (as shown in Figure S5b). However, an obvious boost in luminance intensity is observed in blue QDs on films with different ratios of DPPE:PVK.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Compared to the neat PVK film, the emission of the blended films exhibits a much narrower and slight red shift in DPPE:PVK films. This indicates a change in the bandgap and the absence of excess heteroemission. ,, The PL peaks of blue QDs on PVK and DPPE:PVK films are identical to the PL peak in the neat blue QDs film, which is observed at 450 nm (as shown in Figure S5b). However, an obvious boost in luminance intensity is observed in blue QDs on films with different ratios of DPPE:PVK.…”
Section: Resultsmentioning
confidence: 71%
“…For example, blended or double-layered HTLs are commonly employed to promote hole injection. In our group, we have demonstrated that the hole injection can be enhanced by blending the small-molecule receptor, 2,4,6-tris­(biphenyl-3-yl)-1,3,5-triazine (T2T), or blue thermally activated delayed fluorescence (TADF) material, 4,5-bis­(carbazol-9-yl)-1,2-dicyanobenzene (2CzPN), with PVK as HTLs, either by forming exciton complexes or through energy-transfer processes. , A similar strategy was applied by Liu et al, who reported a unique charge injection at the interfaces between HTLs and QDs layer by blending 1,1-bis­[4-[ N , N′ -bis­( p -tolylamino)­phenyl]-cyclohexane] (TAPC) with PVK as HTL . In addition, a double-layered HTL consisting of PVK and poly­[(9,9-dioctylfluorenyl-2,7-diyl)- co -(4,4′-( N -( p -butylphenyl))-diphenylamine)]­(TFB) in blue QLEDs was reported by Cao et al and Chen et al, which reduced the efficiency roll-off, improved the EQE, as well as reduced the turn-on voltage. , …”
Section: Introductionmentioning
confidence: 99%
“…Further enhancement of the charge carrier mobility within the candidates' films may be achieved via doping and composite engineering. 47 Particular attention should be devoted to the formation of polaron states, which may impact the HOMO level of the HTMs. Given the possibility of charge accumulation at the interface of HTL/ EML, high densities of polaron states may influence the inter-layer energy mismatch and charge transport to the EML, and the overall device performance by, e.g., exciton−polaron quenching.…”
Section: Resultsmentioning
confidence: 99%
“…These results, along with the low HOMO levels of the candidates, may point to the potential use of the materials for promoting the hole injection into QDs and improving the charge carrier balance within the emitting layers. Further enhancement of the charge carrier mobility within the candidates’ films may be achieved via doping and composite engineering . Particular attention should be devoted to the formation of polaron states, which may impact the HOMO level of the HTMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation